(untitled) (Diametros, 2014)
Kant commentators have recently begun to pay attention to Kant’s account of friendship. They have asked questions, such as: Is his description of friendship consistent and robust and does it provide an account of friendship that satisfies common intuitions and expectations of friendship? Their answers to these questions have often been negative. At the same time, many of these critics share a common understanding of two basic aspects of Kant’s account of friendship. Kant sees friendship as both a duty and an ideal state. One critic, Patricia Flynn, considers the implications of this dual claim. She argues that the view that friendship is both duty and idea gives rise to a tension in the concept of friendship. This tension makes the duty of friendship different from all other Kantian moral duties and leaves us with a duty that we cannot achieve. My aim is to revisit Flynn’s argument and by reassessing Kant’s claims to show that there is indeed complexity in Kant’s understanding of friendship, but there is no conceptual problem that makes friendship a duty unlike all other duties or makes it an impossible duty.